Optimizing MSME Performance Through Implementing Effective Human Resource Management Practices in the Creative Industries Sector : Systematic Literature Review (SLR) - Sutomo Sutomo; Sudarmiatin Sudarmiatin; Ludi Wishnu Wardana (International Journal of Management Research and Economics, 2023)
MSMEs, in particular in sector industry creative , have become bone back economy in many countries. Although sector industry creative show potency significant growth , MSMEs in it often experience various obstacles , such as lack of effective management . Problem management source Power HR people don't optimized can become obstacle Serious in reach performance maximum . Application practice management source Power effective human beings in MSMEs can become a key strategy For overcome challenge the . Urgency study This give insightful and informed views about HRM practices that can adopted by MSMEs in the sector This . Method used in study This is Systematic Literature Review (SLR) with collect and analyze related journals with keywords . Based on studies literature conducted , found that understanding deep about connection between HRM practices and MSME performance in context industry creative . Of a number investigated literature , can concluded that proper implementation of HRM can give impact significant positive to MSME performance in the sector This . Recruitment and selection creative identified as step crucial start . Through results MSMEs can get this attract and retain individual with talent suitably creative with demands industry dynamic creative . Research also shows that development Skills creative through training programs is factor decider in increase Power MSME competitiveness and innovation . Findings This give substantial and relevant insights for practitioner business , stakeholders interests , and researchers For optimizing HRM practices with consider context unique industry creative . Implications from study This is that effective HRM implementation can become pusher growth and sustainability of MSMEs, strengthening position they 're inside industry continued creativity.